Saberes para ensinar matemática no estágio supervisionado da Licenciatura em Matemática da UNEMAT – Campus de Sinop (1990 – 2016) - Evangelista, Celma Ramos (2019)
During a considerable period of the history, the teachers’ graduation courses prioritized disciplinary knowledge, they believed it would be enough for the mathematics teaching. However, the emphasis in the disciplinary knowledge, to the detriment of the knowledge of the pedagogical didactic character, has arised important debates in scope on the teachers graduation, among them which is considered the professional knowledge resulting from the articulation between the knowledge of teaching and for teaching, having as an objective to understand the knowledge considered fundamental in the Mathematics teachers graduation and they were mobilized in the Supervised Trainee In Degree in Mathematics of the UNEMAT, Campus of Sinop/MT, in the period from 1990 to 2016. The study was supported in theorical referentials about professional knowledge, (HOFSTETTER, 2017 and VALENTE, 2017), among others, which discuss the teaching profession (GATTI, p 2009; SAVIANI, 2009; FIORENTINI, 2013), as well as in historian references in the culture history and the school disciplines (JULIA, 2001; CHERVEL,1990), especially in the mathematics education historian mothodologic theoretical contribution (VALENTE, 2007; PINTO, 2014). Having in consideration these studies, a work hypothesis where the knowledge to teach mathematics mobolized in the stage in question, while cultural objects, aren’t static knowledge. In composing historically and incorporating advances of science education, they present brands of transformation which respond to the chalenges put for a society in constant change. The perspective accomplished of the historical culture, the study constituted their foundations with documents of official legislation to the degree courses and scholar documents, as pedagogical- political projects in the Mathematics Degree in UNEMAT, Campus of Sinop/MT, reports of the Supervised Trainee and testimonies of supervisors trainee teachers and coordinators of Degree in Mathematics, protagonists who lived the transformation occurred in the trainee activities planned for the referred period. The analysis show that, in consequence of the trainee, knowledge were put to teach mathematics with few evidences of a necessary articulation with the knowledge to teach, capable of setting them up as professional knowledge, according to the concept adopted by (Hofstetter, 2017 and Valente, 2017), such movement, however, permits to verify transformation which have occurred in the Mathematics Educational Field and consequently in the Supervised Trainee, in relation to the presence of professional knowledge, fundamental for the teacher who teaches mathematics in the basic education.